The SCFFBXO3 ubiquitin E3 ligase regulates inflammation in atherosclerosis. (January 2019) - Chandra, Divay; Londino, James; Alexander, Shaun; Bednash, Joseph S.; Zhang, Yingze; Friedlander, Robert M.; Daskivich, Grant; Carlisle, Diane L.; Lariviere, William R.; Nakassa, Ana Carolina Igami; Ross, Mark; St. Croix, Claudette; et al.
Abstract: Inflammation is critical in the pathobiology of atherosclerosis. An essential player in the inflammatory process in atherosclerosis are macrophages that scavenge oxidatively modified low-density lipoproteins (OxLDL) deposited in the subendothelium of systemic arteries that secrete a myriad of pro-inflammatory mediators. Here, we identified that a subunit of the Skp-Cullin-F-box ubiquitin E3 ligase apparatus, termed FBXO3, modulates the inflammatory response in atherosclerosis. Specifically, individuals with a hypofunctioning genetic variant of FBXO3 develop less atherosclerosis. FBXO3 protein is present in cells of monocytic lineage within carotid plaques and its levels increase in those with symptomatic compared with asymptomatic atherosclerosis. Further, cellular depletion or small molecule inhibition of FBXO3 significantly reduced the inflammatory response to OxLDL by macrophages without altering OxLDL uptake. Thus, FBXO3 potentiates vascular inflammation and atherosclerosis that can be effectively mitigated by a small molecule inhibitor.